2022
DOI: 10.1007/s11356-022-21992-3
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the effectiveness of environmental policy stringency and environmental law on environmental performance: does asymmetry matter?

Abstract: Environmental stringency policy shocks and environmental tax have become fundamental policy tools for mitigating the degradation of the environment. The study explores the effects of environmental tax and environmental stringency policy shocks in the reduction of pollution emissions in China for the time 1993 to 2019. This study is a pioneer in assessing the simultaneous impact of these two policy instruments on pollution emissions in China. For empirical investigation, the study employed NARDL estimation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Data for this variable is sourced from the WTO. Following Chen et al [ 51 ], we also measure environmental pollution (EP) using four proxy variables: carbon dioxide (CO2) emissions in kilotons, methane (CH4) emissions in kilotons of CO2 equivalent, nitrous oxide (NO2) emissions in thousand metric tons of CO2 equivalent, and sulfur hexafluoride (SF6) gas emissions, also in thousand metric tons of CO2 equivalent. In addition to these core variables, we include two control parameters in our model: institutional quality (IQ) and gross domestic product (GDP).…”
Section: Datamentioning
confidence: 99%
“…Data for this variable is sourced from the WTO. Following Chen et al [ 51 ], we also measure environmental pollution (EP) using four proxy variables: carbon dioxide (CO2) emissions in kilotons, methane (CH4) emissions in kilotons of CO2 equivalent, nitrous oxide (NO2) emissions in thousand metric tons of CO2 equivalent, and sulfur hexafluoride (SF6) gas emissions, also in thousand metric tons of CO2 equivalent. In addition to these core variables, we include two control parameters in our model: institutional quality (IQ) and gross domestic product (GDP).…”
Section: Datamentioning
confidence: 99%
“…Ahmed ( 2020 ) found that increasing environmental policy stringency led to a decrease in carbon emissions by promoting the use of green technology in 20 OECD countries. Chen et al ( 2022 ) analyzed the relationship between the environmental stringency index and various environmental pollution indicators in China during the period of 1993–2019. Using the NARDL method, the long-term findings showed that positive shocks in environmental policy stringency reduced carbon emissions by 0.94% and greenhouse gas emissions by 0.77%, while negative shocks in environmental policy stringency increased N2O emissions by 0.17%, PM2.5 emissions by 0.50%, and carbon emissions by 0.63%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have recently been more studies on the impact of the environmental policy stringency index (EPSI) on climate change, as seen in studies like Li et al ( 2022b ), Kruse et al ( 2022 ), Wen et al ( 2022 ), Wang et al ( 2022 ), Hassan et al ( 2022 ), Udeagha and Ngepah ( 2023 ), Tariq and Xu ( 2022 ), and Yirong ( 2022 ). As stated by Chen et al ( 2022 ), the index is based on the execution of different policies based on the market, non-market, and technology. EPSI combines different environmental policy indicators, including those for energy and transportation (Botta and Koźluk 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The environmentally stringent rules and regulations aim to amend individual and organizational behavior in carbon emission (CO 2 ) mitigation by promoting consumption of less-polluting energy [14]. Most scholars have shown that environmentally stringent policy is effective in eliminating carbon dioxide emissions (CO 2 ) [3,[15][16][17] and boosting renewable energy production [18][19][20], but no research has found the effect of the Environmental Policy Stringency Index on energy transition. However, the main purpose of this current research is to analyze the impact of the Environmental Policy Stringency Index, technological innovation, foreign direct investment, and eco-innovation on energy transition in newly industrialized countries.…”
Section: Introductionmentioning
confidence: 99%